Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006964.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for communicating contraceptive effectiveness

Abstract: We have limited evidence about what works to help consumers choose an appropriate contraceptive method. For presenting pregnancy risk data, one trial showed that categories were better than numbers. In another trial, audiovisual aids worked better than the usual oral presentation. Strategies for communicating information should be examined in clinical settings and assessed for effect on contraceptive choice and retention of knowledge. To expand the knowledge base of what works in contraceptive counseling, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…This means that structured counseling provided in the modern contraceptives service could increase the participation 6.167 times compared to the standard counseling. Similar result was shown by Lopez LM, 13 2 Randomize Control Trial study showed women who did counseling two times likely to use modern contraceptives than the control group (OR =2.35; 95% CI: 1.82 to 3.03), the method sterilization, the pill, injections, intra uterine devices (IUDs) or methods barrier. Implementation of counseling with information and contraceptive services qualified on the client can increase the effectiveness of contraceptive use.…”
Section: Simanjuntak Lestari Anwar the Effect Of Structured Counsesupporting
confidence: 81%
“…This means that structured counseling provided in the modern contraceptives service could increase the participation 6.167 times compared to the standard counseling. Similar result was shown by Lopez LM, 13 2 Randomize Control Trial study showed women who did counseling two times likely to use modern contraceptives than the control group (OR =2.35; 95% CI: 1.82 to 3.03), the method sterilization, the pill, injections, intra uterine devices (IUDs) or methods barrier. Implementation of counseling with information and contraceptive services qualified on the client can increase the effectiveness of contraceptive use.…”
Section: Simanjuntak Lestari Anwar the Effect Of Structured Counsesupporting
confidence: 81%
“…(37) Welldesigned leaflets and other audiovisual aids can be used to complement the personal interaction couples have with the healthcare provider during counselling sessions. (38) An online contraception advice service could also be set up to provide easy access to reliable and accurate information about contraception. We also recommend that opportunistic contraception education be offered to all women of child-bearing age during their general visits to healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review of strategies to communicate contraceptive effectiveness found limited evidence regarding which counseling tools work best. 3 Steiner, et al, showed that a World Health Organization (WHO) developed chart of contraceptive effectiveness stratified by “average” (typical) versus “correct and consistent use” (perfect use) was significantly more difficult for women to understand. 18 The most recently published WHO chart of contraceptive effectiveness (Figure 3) uses a continuum of typical use effectiveness to demonstrate the difference between the more effective and less effective methods.…”
Section: Commentmentioning
confidence: 99%
“…1, 2 General contraceptive knowledge varies widely across populations with notable disparities among minority and younger populations who have less awareness and understanding of various contraceptive methods. 1-3 Multiple studies have evaluated women's knowledge of a specific contraceptive method, such as the intrauterine device (IUD), 1, 2, 4 or evaluated the knowledge of women in countries outside the United States 5, 6 .…”
Section: Introductionmentioning
confidence: 99%